2016
DOI: 10.1155/2016/7392603
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Reducedγ-Tocopherol Content in Ethiopian Mustard Seeds

Abstract: Ethiopian mustard (Brassica carinata A. Braun) line BCT-6, with reduced γ-tocopherol content in the seeds, has been previously developed. The objective of this research was to conduct a genetic analysis of seed tocopherols in this line. BCT-6 was crossed with the conventional line C-101 and the F1, F2, and BC plant generations were analyzed. Generation mean analysis using individual scaling tests indicated that reduced γ-tocopherol content fitted an additive-dominant genetic model with predominance of additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(57 reference statements)
1
1
0
Order By: Relevance
“…This is the first report on the inheritance pattern of different tocopherol forms in Indian mustard. Previously, the recessive nature of alleles was also reported in B. carinata [19] and a single recessive locus Tph2 for high GTC in sunflower [20]. The frequency distribution of tocopherol content of different forms in the F 2 population developed by RLC3 × NPJ203 (Figure 2) highlighted a skewed distribution pattern by ATC towards the parent RLC3; however, GTC and TTC showed a near-normal distribution.…”
Section: The Inheritance Pattern Of Tocopherol Contentssupporting
confidence: 58%
See 1 more Smart Citation
“…This is the first report on the inheritance pattern of different tocopherol forms in Indian mustard. Previously, the recessive nature of alleles was also reported in B. carinata [19] and a single recessive locus Tph2 for high GTC in sunflower [20]. The frequency distribution of tocopherol content of different forms in the F 2 population developed by RLC3 × NPJ203 (Figure 2) highlighted a skewed distribution pattern by ATC towards the parent RLC3; however, GTC and TTC showed a near-normal distribution.…”
Section: The Inheritance Pattern Of Tocopherol Contentssupporting
confidence: 58%
“…Gene effects from the six-parameter model revealed that mean [m] and additive effects [d] were significant for all studied traits. Earlier, tocopherol content was also reported with the predominance of an additive effect in rapeseed [1,3,11,19]. Other gene effects such as dominance effect [h], additive × additive [i], additive × dominance [j], and dominance × dominance [l] were non-significant for GTC and TTC.…”
Section: The Significance Of [M] [D] [H]mentioning
confidence: 96%